Observations and foreign policy implications of the 2022 American midterm elections - Overby, L. Marvin (2023)
President Joe Biden and the Democratic Party defied strong political headwinds and expectations in the midterm elections to retain control of the Senate and lose the House of Representatives only narrowly. The results indicate that the US might be past peak Trumpism and that the bipartisan consensus on competition with China will be preserved despite divided government in the next two years.